Effect of thermal radiation on MHD natural convective transport of micropolar fluid through a perforated sheet: An unsteady approach - Md. Hasanuzzaman; Md.Abul Kalam Azad; Md.Mosharof Hossain; Bappi Mridha; Mohammed Abdur Rahman (International Journal of Thermofluids, 2025)
In the present investigation, the influence of thermal radiation on time-dependent MHD-free convection of micropolar fluid flow through a perforated sheet is analyzed. To obtain the mathematical solutions, the set of nonlinear ordinary differential equations (ODEs) has been converted from governing partial differential equations (PDEs). The shooting method in the MATLAB environment is then utilized to resolve the transformed system. The influences of several physical parameters upon concentration, temperature, microrotation, and dimensionless velocity profiles are deliberated and revealed graphically. When the thermal radiation (R) is high, it indicates that surface couple stress h′(0)) and local skin friction (f′(0)) are enhanced, but the heat transfer rate (− θ′(0)) is reduced. So, the velocity and the temperature are lifted up, but the microrotation is slowed down for higher amounts of R. The amounts of (f′(0)) and h′(0)) advance by about 25 % and 24 % but reduce the heat transfer rate by about 41 % for growing levels of R (1.0–4.0). With some restrictions, the results are contrasted with previous research. The outcomes agree well with the existing ones.